Pengembangan Perangkat Pembelajaran Aritmetika Sosial Berbasis Problem Based Learning di Kelas VII SMP - Ridwan, Ruslan; Zulkardi, Zulkardi; Darmawijoyo, Darmawijoyo (Jurnal Elemen, 2016)
The purpose of this study is aimeds to (1) produce the mathematics lesson plan based on social arithmetic Problem Based Learning (PBL) in class VII in viewed from the aspects of validity and practicality and to know the potential effects arising from the development of the lesson plan, (2) describe the characteristics of the lesson plan based on social arithmetic Problem Based Learning. The method of the study was the development research according to the type of formative research by Tessmer. The stages of development wereÂ  Self Evaluation, prototyping and product. The subjects were VII.1 grade students of SMP Negeri 1 Muaradua semester 2014/2015 academic year, consistive of 31 people. Data collection techniques used were documentation, walk-throughs, observation sheets, and test results. Data were analyzed qualitatively and quantitatively. The results of data analysis showed that in the mathematics lesson plan based on social arithmetic Problem Based Learning (PBL) were valid, practical, and had a potential effect. The lesson plan had a valid learning in the content, construct, and language experts based on the results of the validation stage of the expert review and the prototypeÂ  test on a small group stage, while the practical lesson plan obtainedÂ  from the revised test results of one-to-one and small group. Potential effects of the lesson plan wasÂ  known from the results of the field test and the results of the students final test. The results of the students final test showed 45.16% of the students were is very good category, 32.26%Â  wereÂ  good category, and 22.58% fair category. From the result of observation, the percentage average of studentsâ activity was above 81,25% included in very good category.